Impact of public debt, bank credit and financial institutions on economic growth: Evidence from selected Asean countries - Azadkhoyrasekh, Saeed; Yahya, M. H.; Kamarudin, F. (Human Resource Management Academic Research Society, 2023)
This study examines the impact of public debt, bank credit and financial institutions on economic growth: evidence from selected ASEAN countries. The need to put the economy on the path of growth and development is more like a complex journey rather than a clear cut path to follow. All the nations of the world have one common aim i.e. to be the most successful economy of the world. Economic growth of every nation is highly dependent on the sustenance and development of its banking. This study tries to examine the relationship between the bank credit and economic growth for six ASEAN countries, Indonesia, Malaysia, Philippines, Singapore, Thailand and Vietnam. It also studies the relationship between development of banking and economic growth for ASEAN countries. Further, the relationship between Public Debt and economic growth is also studied. Changes in GDP indicate the economic growth or backwardness of each country. The finding indicates that the economic growth of the countries are strongly related with the bank credit and public debt status and the economic growth of the chosen countries is weakly related with the banks of the countries. It is thus concluded that bank credit and public debt is more significant variable for economic growth of the countries as compared with that of banks of the countries.